Rapid Determination of Sildenafil and Its Analogues in Dietary Supplements Using Gas Chromatography-Triple Quadrupole Mass Spectrometry - Siti Umairah, Mokhtar; Chin, S. -T.; Kee, C. L.; Low, M. Y.; Drummer, O. H.; Marriott, P. J. (Elsevier Ltd., 2016)
Application of gas chromatography–triple quadrupole mass spectrometry for identification, confirmation and quantification of 6 phosphodiesterase-5 (PDE-5) inhibitors (sildenafil, dimethylsildenafil, homosildenafil, thiosildenafil, thiodimethylsildenafil and thiohomosildenafil) in dietary supplements was investigated. The MS was operated in multiple reaction monitoring mode, for better sensitivity and selectivity. In this manner, the method is adequate to reduce background noise with less interference from co-eluting compounds in the samples. Two different ionisation techniques, electron ionisation (EI) and chemical ionisation (CI), were studied and compared. The chromatographic separation was performed on a short 10 m non-polar capillary column without any derivatisation step. This permitted fast analysis for all analogues with retention time less than 11 min, for both techniques. Use of backflushing can aid method retention time reduction and improves column maintenance. Evaluation of method validation included limit of detection (LOD), lower limit of quantitation (LLOQ), linearity, precision and recovery were performed for both EI and CI techniques. The LOD obtained varied from 0.03 to 1.50 μg/g and the LLOQ ranged from 0.10 to 5.00 μg/g. Good calibration linearity was obtained for all analogues for both techniques, with correlation coefficients (r2) higher than 0.99. Mean recoveries of all analogues using CI show higher values (83.4–108.8%) than that of EI (61.9–91.1%). The intra- and inter-assay precisions were evaluated for all analogues at spiked concentration of 10 μg/g and the relative standard deviation was less than 15% for both methods. These methods were then successfully applied to dietary supplement samples without prior derivatisation, confirming that the samples were adulterated with sildenafil and/or its analogues.